Does board activeness strengthen the relationship between structure of corporate ownership and firm performance? - Yuan, Feng; Hussain, Rana Tanveer; Khalid, Iqra; Li, Mi (Frontiers in Psychology, 2023)
This study empirically investigates the moderating effect of board activeness between the relation of the structure of corporate ownership and firm performance. The objective was evaluated by applying the hierarchal panel regressions taking the data of non-financial companies of the Pakistan Stock Exchange for the period of 2009-18, operationalizing the ownership structure as state ownership, associated companies, foreign ownership, ownership concentration, institutional ownership, and family ownership, and firm performance as operating performance, financial performance, and stock market performance. The findings of the study revealed that operating, financial and stock market performance was favorably influenced by the ownership stakes of the state, associated concerns, institutions, and foreigners. Family interests proved varied for the firm performance. The isolated effect of the board consistently uplifted the firm productivity but its interactional impact with all the ownership stakeholders postulated differential outcomes for internal and external performance. The study provides valuable insights for policymakers and investors to make optimal strategies to manage ownership interests and enhance their value.